Regulatory Oversight of Ageing Management and Long Term Operation Programme of Nuclear Power Plants. (Safety reports series, 2022)
"As Member States seek to extend the operating lifetime of nuclear power plants beyond that which was originally licensed, safety oversight of ageing management and long term operation (LTO) has become increasingly important. This Safety Report provides technical and practical information based on existing regulatory approaches and practices of Member States, and the application of the IAEA Safety Standards. This includes requirements and pre-conditions of the regulatory body for LTO, authorization processes applied to LTO, and regulatory practices and documentation to prepare for and implement LTO. The report is intended for nuclear safety authorities, operating organizations, licensees, manufacturers, designers and technical support organizations considering authorization for LTO of nuclear power plants."--Publisher's description.